Qualitative study of paediatricians’ experiences in the care process for preschool children with complex needs: an example of paediatric care in Croatia - Aida Mujkić; Aleksandar Dzakula; Maja Banadinović; Iva Lukačević Lovrenčić (BMJ Open)
Objectives Preschool children with complex needs require a multidimensional care model. In such a model, paediatricians are one of the key stakeholders. This study examines Croatian paediatricians’ experiences and perceptions of their role in the care process. It explores their view of the other stakeholders, practices and determinants that influence their role and overall quality of care.Design A desk review was performed as the first part of the research. It included a search of electronic bibliographic databases using a structured set of keywords and an analysis of selected strategic, policy and legislative documents, registers, guidelines and reports related to the research topic. This part of the research helped form the research protocol for the two focus groups that followed.Participants 12 primary, secondary and tertiary care paediatricians participated in the focus groups, following the criteria: specialist paediatric experience longer than 5 years, active work status in the healthcare system at the primary, secondary or tertiary level, personal experience of working with preschool children with complex needs.Results The first part of the research identified structural shortcomings, ambiguity in defining systematic approaches to care processes, quality challenges and a lack of multidimensional evaluation in the care system. Focus groups provided insight into the everyday dynamics of those challenges from the paediatricians’ point of view. Six themes emerged from the analysis of the focus groups: (1) profile and needs of preschool children with complex needs; (2) parents in the process of care from the paediatrician’s perception; (3) the role of paediatricians in the process of caring for a preschool child with complex needs; (4) the absolute and relative scarcity of public resources; (5) the need for systematic solutions; (6) the importance of personal engagement.Conclusions Integration, coordination and continuity of care for preschool children with complex needs cannot be achieved by merely focusing on providing enough human and infrastructural resources. Without clear insight into the interrelation of structural inputs and stakeholders’ specific standpoints, we risk further fragmentation and a decrease in the quality of care.